DE-FACTO INTEGRATION OF EAST ASIA COMPARED - Abe, Kiyoshi (Journal of European Economy, 2018)
Despite many barriers, there has been a rise of intra-East-Asia trade. Japanese multinational companies are significant promoters of the de-facto integration, enhancing local procurements and orchestrating the mutual-supply network throughout East Asia. All that a Southeast Asian country needs to do is to plug in the intricate rise of intra-East-Asia trade. Japanese multinational companies are significant promoters of the de-facto integration, enhancing local procurements and orchestrating the mutual-supply network throughout East Asia. All that a Southeast Asian country needs to do is to plug in the intricate production network led by the MNC. Market dynamics functions well in East Asia, whereas political decisions prevail in the ELI. When Japanese MNCs relocate, so does their vertical relationship. Many informal business relationships are active and interwoven in East Asia unlike the ELI.